2018
DOI: 10.1111/1365-2664.13102
|View full text |Cite
|
Sign up to set email alerts
|

Responses of macroinvertebrate communities to small dam removals: Implications for bioassessment and restoration

Abstract: Small dam removals are increasing on a global scale; yet, general predictions of organism response to dam removal are constrained by heterogeneity of study designs, implementation strategies, geographies, and characteristics of dams and their removals. Macroinvertebrate data extracted from 29 studies including 34 small dam removals over a broad geographical range were re‐analysed utilizing dam removal effect sizes (a quantified change from before to after removal). Effect sizes of 10 metrics of community struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 62 publications
0
22
0
Order By: Relevance
“…(c) Results obtained from db-RDA for the morphological dataset based on abundance. The purple arrows represent different species; the red arrows represent environmental variables, in which WaterPol and Sediment represent pollution levels in the water column and sediments, respectively reasons (e.g., Carlson, Donadi, & Sandin, 2018;Pandey et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…(c) Results obtained from db-RDA for the morphological dataset based on abundance. The purple arrows represent different species; the red arrows represent environmental variables, in which WaterPol and Sediment represent pollution levels in the water column and sediments, respectively reasons (e.g., Carlson, Donadi, & Sandin, 2018;Pandey et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of aquatic invertebrate and fish responses to dam removal generally support this trajectory (Bushaw-Newton et al 2002, Stanley et al 2002, Dorobek et al 2015). In a meta-analysis of numerous dam removals, Carlson and colleagues (2018) found that lentic invertebrates first declined in density after dam removal but subsequently recovered within 15–20 months. During the recovery phase, lotic invertebrate taxa, such as EPT, tended to become more prevalent (Bushaw‐Newton et al 2002), attaining community assemblages similar to upstream free-flowing reference sites (e.g., Stanley et al 2002).…”
Section: Within the Former Reservoir: Ponds To Riversmentioning
confidence: 99%
“…Our study focused on the short-term sediment impacts to aquatic food webs during the three years of active dam removal (WYs 2012-2014). Many studies have investigated the effects of dam removal on benthic invertebrates (reviewed by [20]), and other predominantly laboratory-based investigations have examined the effects of increased turbidity and bed disturbance on salmonid foraging [21][22][23]. However, we are not aware of any published studies that have investigated the coupled effects of dam removal on prey availability and prey consumption.…”
Section: Introductionmentioning
confidence: 99%